The impact of partnership transformation on the viability of community-based hybrid corn farming in Ponorogo: A qualitative analysis of the "Tani Mulyo" farmer group - Niskala, Hafizh Ahmad; Hendrayana, Febri; Muis, Zeni Zainal; Maskur, Camal Adi (AGROMIX, 2026)
.